Radiofrequency Ablation for Treatment of Refractory Gastric Antral Vascular Ectasia: A Systematic Review of the Literature. (1st August 2017) - Maida, M.; Camilleri, S.; Manganaro, M.; Garufi, S.; Scarpulla, G.
Abstract : Background and Study Aims . GAVE is an uncommon cause of upper nonvariceal bleeding and often manifests itself as occult bleeding with chronic anemia. To date, the standard of care for GAVE is endoscopic treatment with thermoablative techniques. Despite good technical results, approximately two thirds of patients remain dependent on transfusions after the therapy. One of the emerging and more promising endoscopic treatments for GAVE is radiofrequency ablation (RFA). The aim of this study is to perform a systematic review of literature in order to assess current evidence supporting the effectiveness of this technique for treatment of refractory GAVE. Materials and Methods . Through electronic search, we identified 14 records, and after removal of duplicates and irrelevant studies, we selected 10 studies on radiofrequency ablation of GAVE: 4 prospective open-label single-center studies, 1 retrospective multicentric study, and 5 case reports. Results . Among all 72 treated patients reported in literature, 74.3% achieved a clinical response, while nonfatal AEs have been reported in 4.2% of cases. Conclusions . Despite some qualitative limitations, all literature data support effectiveness of RFA for treatment of refractory GAVE. In the future, large prospective controlled trials with adequate follow-up are needed to better assess the effectiveness and safety of this procedure.